Penyuluhan Hukum Maritim Bagi Nelayan dan Masyarakat Pesisir dalam Pengawasan Kapal Asing di Wilayah Perairan Batam - Fadlan Fadlan; E. Arinda Chikita; Erniyanti Erniyanti (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
This community service activity aims to provide an understanding of maritime law to fishermen and coastal communities in Setokok Village, Bulang District, Batam City, specifically regarding the supervision of foreign vessels in Indonesian waters. The methods used were direct outreach with a participatory approach, group discussions, and case simulations. This activity involved 85 participants consisting of fishermen, community leaders, and village officials. The results of the activity showed an increase in participants' understanding of the rights and obligations of fishermen, procedures for reporting foreign vessels, and the importance of maintaining the sovereignty of Indonesian waters. This activity had a positive impact in the form of increased awareness of maritime law and community participation in monitoring water areas.